Solar ventilation fan - Faradilla, Mod Yatim (2010)
Malaysia is in the climatic region of tropical rainforest and is hot and humid throughout the year. Daily temperature exceeds more than 25°C for 58% of the time with a mean annual humidity of 83%. The high level of global solar radiation ranges from 12 MJm-2day-1 to 21 MJm-2day-1. This project presents the description and the performance curves of a natural draft solar fan that suits the ventilation requirements houses in Malaysia. Unfortunately, the usual ventilation fan in market required almost strong wind to let it operates smoothly therefore whenever wind is slow the ventilation fan is slow. In this project, the developed solar fan utilizes the abundant sun energy (fan heating load) to induce upward air flow due to buoyancy forces and hopefully to resolve the hot attic space issue. The solar house ventilation fan was designed to operate automatically anytime temperature detector detects any temperature changes. This ventilation system that proposed this passive and therefore requires minimum maintenance, minimum operation skill, no electricity, decreasing the usage of air-conditioner, save the environment, but highly valued for consumer money.